COVID-19 and the cardiovascular system: a study of pathophysiology and interpopulation variability - Zhao, Yifan; Han, Xiaorong; Li, Cheng; Liu, Yucheng; Cheng, Jiayu; Adhikari, Binay Kumar; Wang, Yonggang (Frontiers in Microbiology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in humans can lead to various degrees of tissue and organ damage, of which cardiovascular system diseases are one of the main manifestations, such as myocarditis, myocardial infarction, and arrhythmia, which threaten the infected population worldwide. These diseases threaten the cardiovascular health of infected populations worldwide. Although the prevalence of coronavirus disease 2019 (COVID-19) has slightly improved with virus mutation and population vaccination, chronic infection, post-infection sequelae, and post-infection severe disease patients still exist, and it is still relevant to study the mechanisms linking COVID-19 to cardiovascular disease (CVD). This article introduces the pathophysiological mechanism of COVID-19-mediated cardiovascular disease and analyzes the mechanism and recent progress of the interaction between SARS-CoV-2 and the cardiovascular system from the roles of angiotensin-converting enzyme 2 (ACE2), cellular and molecular mechanisms, endothelial dysfunction, insulin resistance, iron homeostasis imbalance, and psychosocial factors, respectively. We also discussed the differences and mechanisms involved in cardiovascular system diseases combined with neocoronavirus infection in different populations and provided a theoretical basis for better disease prevention and management.